Increase of the Single-Shaft Power Microturbine Unit Capacity by Installing the Rotor on Hybrid Air Bearings - VolobuevI.A.; Bulat P.V.; ProdanN.V. (Problems of the Regional Energetics, 2018)
The problem of increase of the unit power on the shaft of an energy microturbine is of current interest. One of the problems is the small single unit power of microturbines, limited by the low capacity of gas-dynamic air bearings. The problem could be solved by replacing gas-dynamic bearings with hybrid ones with a higher load-bearing capacity. Hybrid bearings use self-aligning turning segments and forcing gas into the lubricating layer. The scientific result of the work is the method of designing grooves that distributes gas, the shape of which repeats the pressure isoline on the segment’s surface when the microturbine is operating at the rated rotation speed. Method is based on solving Reynolds equations for a thin lubricating layer at the grooves. The developed system of grooves provides static stability of the segment in stationary modes and dynamic in transient modes, vibration suppression, automatic response to changes in load and speed. The calculation method allows finding the optimum thickness of the lubricant layer for a given accuracy of shaft and segment manufacture. It is shown that the load-bearing capacity is maximal when the resultant forces act on a segment, and not between segments. Numerical calculations and experiments have shown that the developed hybrid bearing has a maximum bearing capacity at a given air flow rate for the power range on the shaft from 200 kW to 2000 kW, with a load on the shaft up to 300 kg and a speed of up to 100.000 rpm.